PEMBUATAN DATA ONLINE SISTEM TENAGA KERJA KONSTRUKSI PROVINSI JAMBI DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN - Ikhsan, Muhammad (LP2M Universitas Nurdin Hamzah, 2017)
Integrated Service Unit of Construction Services Area as a container that serves as a place to carry out the process of training, testing and development of Manpower Construction Services. However, still doing the process of data processing and dissemination of information in a non-computerized. Data processing is still done in this way causing some problems and constraints, including the processing of administrative data that takes a lot of time, the resulting information is still less accurate. The method used in the compilation of data and information is done by survey data which includes primary data and secondary data. The design of an online database system includes contractor data processing, consultant data, Skill Certificate data, Expertise Certificate, Construction Enterprise Data integrated in an online database. Based on the research done, it can be concluded that the data processing and information process are non-computerized, not yet integrated and the online database created displaying info such as profile, Skilled Power Data, Data Experts, online training list, vision and mission.